263. Antibody Spill-Over vs. True Coccidioidal Meningitis in a Patient with HIV/AIDS and Disseminated Coccidioidomycosis. (4th December 2021) - Newby, Renee E; Sam, Danny L; Cooper, Joseph
Abstract: Background: The diagnosis of coccidioidal meningitis merits life-long antifungal therapy given high rates of disease recurrence. Accurate diagnosis is important. Antibody spill-over into cerebrospinal fluid (CSF) can happen when serum titers are high. We present a case of antibody spill-over vs. true fluconazole-resistant coccidioidal meningitis. Methods: A 49-year-old man presented with 6 months of intermittent fever, myalgias, decreased appetite, vomiting, diarrhea, unsteadiness and 60-pound weight loss. He was recently diagnosed with HIV and a prior lymph node biopsy had grown Coccidioides immitis ( C. i ) for which he was given fluconazole 100 mg twice daily. Figure 1. Timeline of Coccidioides immitis lab results in relation to treatment regimen. CF: Complement fixation, EIA: Enzyme immunoassay for Coccidioides antigen, CSF: Cerebrospinal fluid, c/mL: copies/mL, R: resistant, S: susceptible. Results: Vitals revealed a temperature of 102°F. He was cachectic and a 0.5 cm right supraclavicular lymph node was palpable. No meningeal signs were appreciated. CD4 count was 50/µL (18%), HIV-1 viral load 2, 969, 945 copies/mL. Computed tomography (CT) of the abdomen/pelvis suggested lung and spleen involvement. Serum C. i enzyme immunoassay (EIA) was 1.38 ng/mL, immunodiffusion (ID) was positive and complement fixation (CF) titer was 1:256. C. i was isolated from expectorated sputum. CSF cell count was normal, but ID was positive and CF titer was 1:2 however, lab reported concern for spill-over due to high serum IgG titers. He left against medical advice with fluconazole 400 mg daily. He was hospitalized a month later for failure to thrive. MRI head revealed enlarged lateral and third ventricles with increased periventricular hyperintensity concerning for coccidioidal meningitis. Repeat serum studies were stable. CSF revealed CF 1:4 and C. i antigen by EIA 1.31ng/mL, distinguishing between spill-over and meningitis. Susceptibility results showed resistance to fluconazole and amphotericin B with minimum inhibitory concentrations (MICs) of 50 and 4 respectively, posaconazole susceptibility (MIC < 1) and itraconazole borderline (MIC 3.7). Despite amphotericin B resistance, it was used for bridge to posaconazole. ART was initiated after concern for immune reconstitution had resolved. Conclusion: This case highlights the difficulty in making an accurate diagnosis of coccidioidal meningitis. It also describes a fluconazole-resistant C. i isolate in the setting of prolonged low-dose fluconazole therapy. Disclosures: All Authors : No reported disclosures